Endoscopic Retrieval of Intraventricular Migrated Whole Ventriculoperitoneal Shunt: A Case Report - Tariq, Muhammad; Shrestha, Diggaj (Nepal Journal of Neuroscience, 2019)
Ventriculoperitoneal shunt is associated with different complications. Mechanical complications like blockage, disconnection and distal migration are relatively common. Distal migration of shunt is well documented. But proximal migration of the shunt into the ventricles is very rare with only a few cases reported in literature. Proximal migration of entire shunt in the ventricle, none of them have been proven. In comparison to frontal burr hole, occipital burr hole could facilitate migration due to relatively straight pathway.